Youth Labor Market Transition Challenges in Western Balkans: The Case of Macedonia, Serbia, and Montenegro - Avni Arifi; Bekim Marmullaku (European Scientific Journal, ESJ, 2019)
The main challenge of Western Balkans countries since in this period of transition has been the unemployment issue. In different time tables the unemployment rate has been 35% but if we see the unemployment rate among youth, its level at times has even been almost twice as higher that the overall unemployment rate. In this paper we will focus on youth unemployment and the challenges they face towards being employed after they finish their education. For this purpose it will be used the data from the School-to-work Transition Survey (SWTS) administered by the International Labor Organization for Macedonia, Serbia, and Montenegro which was conducted during 2014. The results will show which factors influence most in being unemployed. The main aim of this paper is to analyze the transition of youth from the education process to labor market and their employment. The results deriving from this paper will shad light to the problems that youth in Western Balkan faces.